IMPLEMENTASI MODEL PjBL BERBANTUAN MEDIA POP-UP BOOK UNTUK MENINGKATKAN KREATIVITAS MURID PADA MATERI BENTANG ALAM - Tri, Yuliana; Sulistyo; Dwi Ferdiani, Rosita; Kukuh Kuncoro, Andriyas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Creativity is an important skill that needs to be developed starting in elementary school. However, initial observations in the third-grade class at SDN Gadang 4 in Malang indicate that students’ creativity in the subjects of Physical Geography and Occupations remains low. Students tend to be passive, lack confidence in expressing their ideas, and struggle to produce original work. This study aims to describe the implementation of the Project-Based Learning (PjBL) model aided by Pop-Up Book media and to determine the increase in student creativity. The study used a two-cycle Classroom Action Research (CAR) method with 27 third-grade students as subjects. Data were collected through observation using a rubric that included indicators of fluency, originality, elaboration, and flexibility. The results showed that the class-wide achievement rate increased from 37.5% in Cycle I to 92.6% in Cycle II, with an average creativity score of 14.04 out of 16 (87.75%). Improvements were observed across all creativity indicators, particularly fluency, originality, elaboration, and flexibility. Thus, the Pop-Up Book assisted PjBL model is effective in enhancing students’ creativity in IPAS learning.